Calculation of Drug Dosage In Chronic Kidney Disease - Tenta Hartian Hendyatama; Nunuk Mardiana (Universitas Airlangga, 2020)
Kidneys are the main organ in fluid and electrolyte homeostasis. It also have an important role in eliminating various types of drugs. Drug elimination in the kidney is affected by plasma drug concentrations, plasma protein binding, and kidney function. Glomerular filtration rate (GFR) represents the kidney function. Thus by knowing it, drug dosage can be determined.Chronic kidney disease alter the effect of drug, some decrease drug effect but more often increase drug toxicity. Chronic kidney disease affect the pharmacodynamic and pharmacokinetic of drug. Therefore, providing an optimal treatment for CKD patient, knowledge of the pharmacokinetic and pharmacodynamic changing in CKD is needed.Exploring the patient's history and carrying out complete physical examination is important before giving the drug to patients with impaired kidney function. In addition, identifying drugs that have the potential to cause nephrotoxicity and drug interactions is also important.The body response to drugs in patient with CKD is very varied, complex, and individual. Dosage must be based on several factors, not only glomerular filtration rates but also other comorbid diseases, interactions with other drugs and clinical condition of the patient.